Optimalisasi Penguasaan Makhorijul Huruf Santri Taman Pendidikan al-Qur’an Melalui Metode Tartila - Cholil, Nailatul Khoiriyah; Hasanah , Uswatul (Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2023)
This research focuses on implementing learning using the Tartila method. The aim of this research is to determine the effect of implementing Al-Qur'an learning using the Tartila method on the makhorijul huruf of TPQ Sabilun Najah students in Kendang Dukuh Village, Wonorejo District, Pasuruan Regency. In this research, the researcher used a descriptive-qualitative approach, which produced a research report containing data quotations to provide an overview of the presentation of the report. This research was carried out in several stages: observation stage, data collection stage, data analysis, and data presentation. The data collection techniques used by researchers were observation, interviews, and documentation. Data analysis techniques are the process of systematically searching and compiling data obtained from interviews, field notes, and documentation. The data analysis processes carried out by researchers are data reduction, data presentation, and data withdrawal. To determine the effect of implementing Al-Qur'an learning using the Tartila method on the literacy skills of TPQ Sabilun Najah students in Kendang Dukuh Village, Wonorejo District, Pasuruan Regency. This research consisted of three learning activities: reciting the Al-Qur'an, and Juz 'amma; the results of observations in the field; and the results of interviews with data sources. Based on the results of the research that has been carried out, it can be concluded that the influence of implementing Al-Qur'an learning using the Tartila method on the makhorijul huruf of TPQ Sabilun Najah students in Kendang Dukuh Village, Wonorejo District, Pasuruan Regency is that it is able to make students read the Al-Qur'an fluently and students are able to recite it. makhorijul huruf properly and correctly in accordance with the rules of the science of recitati.